Evaluation of real-time video from the digital indirect ophthalmoscope for telemedicine consultations in retinopathy of prematurity. (August 2022) - Ho, Tiffany; Lee, Thomas C; Choe, Ja-Yoon; Nallasamy, Sudha
Introduction: This study aimed to evaluate the validity of using real-time video indirect ophthalmoscopy for telemedicine consultations for paediatric retinal findings, using retinopathy of prematurity (ROP) as a model disease. Methods: An ophthalmologist simultaneously performed and recorded routine ROP screenings on enrolled premature infants (aged ≤30 weeks and weighing <1500 g) using the Keeler digital indirect ophthalmoscope. Examinations were graded as no ROP, mild, type 1 or type 2. Masked to clinical findings, another ophthalmologist reviewed and graded streamed video feed transmitted at 4096 kbps. We compared the sensitivity and specificity of diagnosing ROP via streamed and stored-and-forwarded video clips to the gold-standard in-person examination. Results: A total of 150 examinations of individual eyes from 34 babies were included. The median postmenstrual age (PMA) at delivery was 24 weeks (range 23–34 weeks), the median birth weight was 630 g (range 455–1530 g) and the median PMA at examination was 37 weeks (range 31–54 weeks). Of those infants with any ROP, the sensitivity and specificity of streamed examinations were 100% and 70.6%, respectively. For type 2 or worse ROP, the sensitivity and specificity were 92.5% and 86.1%, respectively. For type 1 ROP, the sensitivity and specificity were 100% and 99.3%, respectively. Sensitivities (unless already 100%) and specificities were slightly higher for store-and-forward evaluations. Discussion: Streamed video feed from the digital indirect ophthalmoscope can be utilised to diagnose clinically significant ROP accurately, though store-and-forward video review yielded slightly better results.